Islamic Welfare State: K.H Abdurrahman Wahid Perspective - Ana Chonitsa; Ahmad Taufiq; Muhammad Mufid (Alfuad: Jurnal Sosial Keagamaan, 2024)
Indonesia is a country rich in abundant natural resources. There are various natural products, biological and non-biological, from various fields and livelihoods. However, the existing resources have not fully made Indonesian people prosperous. The data shows that unemployment and crime in Indonesia are very high. Therefore, it is necessary to analyze the real concept of prosperity in Indonesia. This type of research is a literature study sourced from books, journals, and scientific articles. The results of the study show that the Islamic welfare state from Gus Dur's perspective is a state that creates prosperity for the Indonesian state both for Islam and as a whole. To overcome existing social problems, it is necessary to apply the values of the characteristics of a prosperous state as Gus Dur has conveyed, namely a law-based prosperous state, a democratic prosperous state, a prosperous country for civil society movements, and a socio-cultural prosperous state by applying these values and characteristics, the Indonesian state can become a Baldatun Thoyibatun Warobbun Ghofur state.